BALB/c and C57BL/6 mouse strains influence gastric function outcomes with administration of cisplatin and dexamethasone - Loyane Almeida Gama; Mariana Pirani Rocha Machado; Luciana Aparecida Corá; Ana Paula Simões Beckmann; Wellington David Luz Alves; José Ricardo de Arruda Miranda; Madileine Francely Américo (Universidade de São Paulo, 2023)
Abstract Our aim was to evaluate the effects of cisplatin and dexamethasone alone and combined on gastric contractility and histomorphometry of BALB/c and C57BL/6 mice. BALB/c and C57BL/6 male mice (8-week-old) were randomly separated into: Control; Cisplatin (7.5 mg/Kg); Dexamethasone (2.0 mg/Kg); and Dexamethasone plus Cisplatin (2.0 mg/Kg of dexamethasone 1-hour prior to 7.5 mg/Kg of cisplatin). Drugs were administered intraperitoneally for three days. Body weight and food intake were evaluated on 2nd day. Alternating Current Biosusceptometry technique was employed to measure gastric contractions on 3rd day. Afterward, mice were killed for gastric histomorphometric analysis. Cisplatin decreased food intake and caused bradygastria in BALB/c mice; however, the amplitude of gastric contractions decreased in both BALB/c and C57BL/6. Dexamethasone and cisplatin combined restored the gastric frequency and food intake only in BALB/c, but drug combination reduced the gastric amplitude of contractions in both strains. Dexamethasone alone increased gastric mucosa thickness in C57BL/6 and decreased muscular thickness in BALB/c. In conclusion, the mouse strains presented differences in acute effects of cisplatin and dexamethasone alone and combined on gastric function. This reinforces the importance of choosing the appropriate mouse strain for studying the acute effects of drugs on the gastrointestinal tract.